THE APPLICATIONS OF ENERGY ALTERNATIVES IN TURKEY USING MULTICRITERIA DECISION MAKING PROCESSES - Balin, Abit; Alcan, Pelin; Basligil, Huseyin (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
As we search to achieve sustainable development and substance, energy security and efficiency should be viewed not only through the perspective of addressing short-term challenges, but also a necessity for long-term growth of the economy. In this paper, PROMETHEE and Electre approaches are suggested for the selection among energy policies. Also, the methodology is based on these two methods via comparison. In the application of the proposed methodologies, the best energy policy is launched into determining for Turkey.
Keywords: Computer Science